SOLID WASTE MANAGEMENT IN CANADA approaches, practices, and experiences. (ROUTLEDGE, 2025)
This edited volume takes a comprehensive look at solid waste management across jurisdictions in Canada, including provinces, territories, municipalities, and Indigenous communities. It provides the reader with an understanding of various solid waste management approaches, policies, practices, barriers, and innovations that are being pursued and developed by jurisdictions to solve their current challenges and improve current systems in place. Solid waste management remains one of the most challenging environmental concerns in the 21st century. Understanding its complexity by bridging theory and practice is essential for current and future management, and for achieving the Sustainable Development Goals. Using a multidisciplinary approach, contributors include social scientists, engineers, economists, scientists, urban planners, and practitioners in the solid waste management field, who utilize qualitative, quantitative, and mixed methods in examining solid waste management issues in Canada. Topics include solid waste management policy and governance, community- based approaches to waste management, waste management in northern, remote, rural, and Indigenous communities, landfill management and stabilization, and innovative and emergent waste management. This book is an important resource for researchers, undergraduate and graduate students, policymakers, solid waste management professionals, government officials, and members of the public interested in solid waste management.
Keywords: Refuse and refuse disposal -- Canada.; Sustainable development.; elektronické knihy; electronic books